A Conceptual Review of the Philosophy of Islamic Education - Mansur (Dirasah: Jurnal Pendidikan Islam, 2025)
The phenomenon of value crisis in the contemporary Islamic education system shows the urgency to review the philosophical foundation that underlies the educational practice. This article aims to critically examine the notion of Islamic education philosophy through a qualitative- contextual approach that is oriented towards the integration of ontological, epistemological, and axiological values in education. Through literature studies and field findings, this article identifies a gap between the ideality of Islamic teachings and educational practices in formal institutions. The philosophy of Islamic education that is only understood normatively is unable to answer the complexity of modern educational challenges, such as secularization of science and dehumanization. This article offers a conceptual framework for an integrative philosophy of Islamic education, emphasizing the importance of revelation, reason, and experience as the basis for developing holistic Islamic education. The findings are expected to make theoretical and practical contributions to the development of a more contextual and transformative Islamic education system.